A Comparative study on decency of employment between specialized vocational high school and meister high school graduates based on the ILO decent work agenda - MOON, Ahlum (KDI School, 2015)
The main purpose of this paper is to examine and compare between employment of conventional and new vocational high school graduates based on the ‘Decent Work’ agenda proposed by International Labor Organization (ILO) and the existing literature. In comparing between the employment decency of vocational high school graduates, this study seeks solutions to challenges that the existing vocational high schools have been facing and opportunities to improve the vocational program and policy arrangements. Therefore, this paper provides the current employment situation of the vocational high school graduates and further suggests policy recommendations in terms of youth employment. The data of the two groups who graduated from ‘Specialized vocational high schools’ (conventional) and ‘Meister high schools’ (new) are drawn from ‘High School Graduates Employment Survey’ (HSGES) and analyzed according to the eight selected indicators: ‘Employment Opportunities’, ‘Adequate earnings’, ‘Decent hours’, ‘Stability and security of work’, ‘Social protection’, ‘Social dialogue and workplace relations’, ‘Fair treatment in employment’, and ‘Job Satisfaction’. This research discovers that the quantity and quality (‘decency’) of employment v for Meister high school graduates is better than that of Specialized high school graduates. In addition, gender differences in the quantity and quality (‘decency’) of employment are examined; female graduates in each group show better decency of employment than their male counterparts. As there were the first-time graduates from Meister high schools in 2013, a follow-up survey of the vocational high school completers should continue so as to make greater progress in vocational education programs, which will help to promote the vocational education program for future vocational high school candidates and develop a career pathway into youth employment. Further studies should be investigated on what led the differences of decency in employment between Meister high school graduates and Specialized vocational high school graduates, and what improvement should be applied to Specialized vocational high school programs.
Thesis(Master) --KDI School:Master of Development Policy,2015